Green Innovation and Digital Transformation: A Strategic Framework for Sustainable International Business - Naghmana Siddique, (Dialogue Social Science Review (DSSR), 2025)
The global business landscape is increasingly shaped by sustainability imperatives, prompting firms to integrate green innovation and digital transformation into their strategic frameworks. This paper explores how emerging digital technologies—such as artificial intelligence (AI), block chain, and the Internet of Things (IoT)—drive sustainability in international business while ensuring regulatory compliance and competitive advantage. It also examines the role of Environmental, Social, and Governance (ESG) principles in aligning technological advancements with long-term environmental and social objectives. Through a comprehensive analysis of case studies and empirical data, this study provides actionable recommendations for businesses and policymakers to foster sustainable digital innovation in a globally competitive environment.